Hospital readiness at Yogyakarta and surrounding areas to implement telepsychiatry - Daniel C.A. Nugroho; Eko Nugroho; Carla Raymondalexas Marchira (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Purpose: This study aims to determine hospitals’ readiness before implementing telepsychiatry.Method: This case study analyses the results of interviews from Head of Psychiatry Department or equivalent, information systems administrator and psychiatrist at 3 Mental Hospitals and 1 General Hospital. Interviews and observations were then compared with related theories.Results: RSJS Magelang does not have adequate infrastructure for telepsychiatry implementation. RSUP Sardjito having difficulties in terms of management, infrastructure and the desire to use telepsychiatry. RSJ Grhasia having obstacles in terms of management and fulfillment of infrastructure needs. RSJD Soedjarwadi does not have any obstacles if they start to implement telepsychiatry.Conclusion: RSJD Soedjarwadi is ready to implement telepsychiatry. As for other hospitals need further improvement, mainly in their infrastructure